Use Of Rasch-andrich’s Rating Scale Model In The Calibrating Of The Depression - عيواج صونيا; زياد رشيد (University of Eloued جامعة الوادي, 2023)
Abstract: The current study aims to calibrate items of the Depression, Anxiety and Stress Scale (DASS42) using Andrich’s Rating Scale model emerged from the family of a the Rasch Unidimensional Measurement Model. The sample consisted of (404) high school students. Data were analyzed, using the statistical programs (Spss v21), and (winsteps v4.0.1). Parameters of the items, parameters of persons, and the standard error of measurement were estimated for both, in addition to the calculation of the statistical index of the Infit (MNSQ) and Outfit (MNSQ) of each item of the Andrich’s Rating Scale model and all the 30 item lies After of the calibrated within an acceptable range of MNSQ value (0.84-1.17).
Anxiety And Stress Scale (dass-42) On High School Students
Keywords: Rasch-Andrich’s Rating Scale model; Calibration; Depression; Anxiety; Stress; DASS42